Sismicidade e correlação com feições geológicas: o caso do lineamento Pernambuco e seu entorno - Lima Neto, Heleno Carlos de (2013)
This thesis presents and discusses the results of the various seismic areas in the State of Pernambuco, with the aim of having a vision of regional seismicity and its causes. To the papers published in journals were added two new original works submitted to international journals, dealing with seismic areas located in the counties of São Caetano, Cupira, and Agrestina. All seismic areas mentioned in this thesis are located on the Pernambuco Lineament and its surroundings (both in branches or single faults within 40 km of it). The Pernambuco Lineament is a Neoproterozoic shear zone of continental-scale that deformed the Borborema Province, and presents as branches, shear zones with NE-SW direction. The new submitted papers are from the analysis of data collected by three local networks of stations that operated in the following areas: network SO07 (seismicity in the district of Santa Luzia - São Caetano, 2007), network BM10 (data from seismic areas of Serra Verde ( Cupira) and Barra do Chata (Agrestina), in 2010), network SO10 (seismicity near the urban center of São Caetano in 2010). These data were used for determining the hypocenters and focal mechanisms in order to discuss the relationship between the seismicity and geological features of the area. The new mechanisms obtained, as well as the previously published allowed the determination of the direction of the average stress in the region. The direction of stress in the region involving the various seismic areas, now or previously studied, is quite stable and approximate EW direction (SHmax). The correlation between seismicity and geological features is observed on the lineament and north of it. In the south (Cupira and Agrestina), in seismic areas nearby shear zones NE-SW, there is no correlation and seismogenic EW normal faults are active and its motion is compatible with regional stresses. It is probable that these active faults are more recent than the Neoproterozoic, probably of the Cretaceous period, when the last great movement of the Pernambuco Lineament occurred